Pharmacognostical evaluation of Launaea sarmentosa (Willd.) schultz-bip.ex Kuntze root - Salih, Yusriyya (Medknow Publications & Media Pvt Ltd, 2013)
Launaea sarmentosa (Willd) Schultz-Bip.ex Kuntze (Asteraceae), locally known as Kulhafila in the Maldives, is a creeping herb, native to tropical Indian coastlines. According to anecdotal evidence from locals in the Maldives, the roots of this plant are used as an ingredient of a popular medicinal preparation (Hilibeys) taken by mothers after childbirth. It is also used in various other ailments in different parts of the Maldives, as well as in India. So far, there has been no scientific documentation of this plant. The only source of information available is held by natives and traditional medical practitioners. The present study was conducted on the root of L. sarmentosa for its pharmacognostical and phytochemical characteristics as per Ayurvedic Pharmacopoea of India (API) parameters. The microscopic characteristics of the root show prismatic crystals, multiseriate medullary rays, laticiferous cells, and pitted parenchyma. Qualitative analyses, such as loss on drying, ash value, pH, etc., were conducted. Preliminary phytochemical screening shows the presence of alkaloids, tannin, steroids, etc.